2015
DOI: 10.1021/acs.chemmater.5b02641
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Multichromophoric Arrays in Organic Photovoltaics

Abstract: A covalently linked multi-chromophoric array (BDP-Por) was used as the donor layer in planar hetero-junction organic photovoltaic (OPV) cells with the structure (ITO/BDPPor/C 60 /BCP//Al, BCP = bathocuproine). BDP-Por is a platinum tetrabenzoporphyrin core (Pt(TPBP)) bonded through the phenyl groups to the meso position of four 4,4-difluoro-3,5-dimethyl-4-bora-3a,4a-diaza-s-indacene (BODIPY) moieties. The OPV outperforms analogous OPVs which use only the Pt(TPBP) as the donor, predominantly by producing a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…18,32 For example, a tandem-layered QD triad solar cell structure was found to produce a 3.0% power conversion efficiency as compared to the 1.65% efficiency for a single-layer large band gap QD solar cell. 19 Multichromophore organic solar cells 33 were found to have short-circuit currents that changed from 2.5 to 4.5 mA/cm 2 when a donor platinum tetrabenzoporphyrin was linked to an organic dye acceptor with an unsaturated bridge. Molecular triad architectures were also shown to have larger ET yields than the yield found in molecular dyad systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,32 For example, a tandem-layered QD triad solar cell structure was found to produce a 3.0% power conversion efficiency as compared to the 1.65% efficiency for a single-layer large band gap QD solar cell. 19 Multichromophore organic solar cells 33 were found to have short-circuit currents that changed from 2.5 to 4.5 mA/cm 2 when a donor platinum tetrabenzoporphyrin was linked to an organic dye acceptor with an unsaturated bridge. Molecular triad architectures were also shown to have larger ET yields than the yield found in molecular dyad systems.…”
Section: Introductionmentioning
confidence: 99%
“…Multilayered QD thin-film solar cells typically exhibit increased energy-conversion efficiencies compared to single-layer cells. ,, The high efficiency of multilayered QD thin films is usually explained by the large short-circuit current that results from the large number of QD absorbers in the device. , For example, a tandem-layered QD triad solar cell structure was found to produce a 3.0% power conversion efficiency as compared to the 1.65% efficiency for a single-layer large band gap QD solar cell . Multichromophore organic solar cells were found to have short-circuit currents that changed from 2.5 to 4.5 mA/cm 2 when a donor platinum tetrabenzoporphyrin was linked to an organic dye acceptor with an unsaturated bridge. Molecular triad architectures were also shown to have larger ET yields than the yield found in molecular dyad systems. In a trilayer organic solar cell, with an ET energy cascade but a flat valence band profile, an ∼2-fold increase in power conversion efficiency was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Three oxygen scavengers were selected here from a vast number of potential candidates, namely, oleic acid (OA), 9,10-dimethylanthracene (DMA), and 2,5-dimethylfuran (DMF). The upconversion system was based on the established red-absorbing triplet photosensitizer platinum­(II) tetraphenyltetrabenzoporphyrin (PtTPBP), synthesized as previously reported, in concert with the highly fluorescent blue/green emitter 9,10-bisphenylethynylanthracene (BPEA, Φ F = 0.94) (Figure ). ,,, Relevant triplet energy transfer parameters and upconversion metrics have been documented to determine the impact of the various components on the ultimate upconversion performance.…”
Section: Introductionmentioning
confidence: 99%
“…Organic semiconductors remain materials of interest in a wide array of fields in both fundamental and applied science. This interest stems from the natural abundance of the elements used to synthesize these materials, as well as their novel physical properties found thus far only in organics, such as singlet fission. , Several research groups have demonstrated the ability to fabricate functional devices such as field-effect transistors, optoelectronic components, and photovoltaic cells using solutions of organic semiconductors . While these solution-based approaches may offer lower costs in both dollars and energy than some of the more traditional approaches for inorganic materials, using a solvent carrier for the active molecular unit introduces a level of complexity to processing not encountered using other methods.…”
Section: Introductionmentioning
confidence: 99%